Elbow의 인장 특성에 미치는 성형 방법의 영향 - 김학철(Hak-Chul Kim); 이기식(Ki-Sik Lee); 탁영준(Young-Joon Tak); 남기우(Ki-Woo Nam); 최병철(Byoung-Chul Choi) (동력시스템공학회지, 2021)
본 연구에서는 STS304L을 이용하여 냉간 및 열간성형으로 제작 된 엘보우의 미세 구조 및 인장 특성을 평가하고 비교하였다. 열간성형 시험편은 오스테나이트 단상을 나타내고, 냉간성형 시험편은 오스테나이트 조직에 약간의 마르텐사이트가 관찰되었다. 냉간 및 열간성형 후에 열처리 한 엘보우도 오스테나이트 단상을 나타내었다. 냉간성형에 의하여 생성된 마르텐사이트는 열처리에 의하여 오스테나이트로 역변환되는 것으로 잘 알려져있다. 냉간성형 시험편은 열간성형 시험편보다 강도가 높지만 연신율이 낮다. 이것은 일부의 오스테나이트가 마르텐사이트로 변형되고, 냉간성형 동안에 생성되는 전위 및 침전물의 원인이 된다. 냉간성형 엘보우의 강도는 약 15% 증가하였고, 연신율은 약 38% 감소하였다. 반면 열간성형 엘보우는 강도와 신율에 큰 변화가 없었다. This study carried out the evaluation and comparison the microstructure and tensile properties of elbow, which is manufactured by the cold and hot forming using STS304L. Hot-formed specimen shows the austenite single-phase, while the cold-formed specimen shows some martensite in austenite structure. Heat treated elbows after the cold- and the hot-forming also show the austenite single-phase. It is well known that the martensite produced by cold forming is inverse transformation into austenite by heat treatment. The cold formed specimen shows higher strength but lower elongation than hot-forming specimen. This is cause to transformation of some austenite into martensite, dislocation, and precipitate generated during cold-forming. The strength of the cold-formed elbow increased by about 15% and the elongation decreased by about 38%, whereas the hot-formed elbow had no significant change in strength and elongation. KCI Citation Count: 0